2006
DOI: 10.1086/506940
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Molecular Characteristics of a Highly Lethal Pneumococcal Meningitis Epidemic in Burkina Faso

Abstract: Intervention strategies during the epidemic season in Burkina Faso (and perhaps elsewhere) must now account for pneumococcal meningitis occurring in an epidemic pattern similar to meningococcal meningitis. Although a serotype 1 clone was commonly isolated, over half of the cases were caused by other serogroups and/or serotypes, and genetic diversification increased over a relatively short period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 25 publications
8
102
0
Order By: Relevance
“…However, the type 1 isolates used in this study were from Sweden, and infections with these clones have not led to fatal outcomes (12). In contrast, a different clonal complex of ST217 dominated invasive serotype 1-mediated disease in sub-Saharan Africa, leading to high lethality (14). Hence, we included a Swedish serotype 1 isolate of ST217 in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the type 1 isolates used in this study were from Sweden, and infections with these clones have not led to fatal outcomes (12). In contrast, a different clonal complex of ST217 dominated invasive serotype 1-mediated disease in sub-Saharan Africa, leading to high lethality (14). Hence, we included a Swedish serotype 1 isolate of ST217 in the study.…”
Section: Discussionmentioning
confidence: 99%
“…51,59 Differences in prevalence of the common infective organisms in patients with sickle cell disease between African and European countries, for example, are crucial to identify since this will dictate the effectiveness of prophylactic measures. Penicillin prophylaxis has played a major role in reducing mortality in developed countries 60 and it is important to find out whether it will be similarly beneficial in African countries where several groups have found that Streptococcus pneumoniae is also a major cause of morbidity and mortality 61,62 whereas others report that it is less common. 63 The growth of research collaborations in sickle cell disease between developing countries and well resourced countries 31,32,[61][62][63] has recently been highlighted as an important tool for improving clinical and diagnostic facilities in developing countries as well as advancing our knowledge of disease pathogenesis.…”
mentioning
confidence: 99%
“…Although the majority of isolates encountered in this investigation were recovered from the south-eastern region, in particular from São (Spratt & Greenwood, 2000). Examples of clonal expansion associated with serotype 1 isolates have been described recently: the epidemic pneumococcal meningitis that occurred in the Africa meningitis belt, specifically in northern Ghana and Burkina Faso, were caused by serotype 1 isolates of the hypervirulent ST217 clonal complex (Leimkugel et al, 2005;Yaro et al, 2006), and the emergence of a single serotype 1 lineage (ST306) was reported among healthy carriers attending day-care centres in Portugal after the introduction of a seven-valent conjugate vaccine (Nunes et al, 2008).…”
Section: Resultsmentioning
confidence: 84%